A Review of Meta-Analyses of Correlation Coefficients on L2 Reading Comprehension - Eun-Hee Jeon; Junko Yamashita (MDPI AG, 2024)
Quantitative meta-analyses have gained popularity among L2 reading researchers in recent years. Meta-analyses, especially meta-analyses that investigate the relationships among variables (e.g., meta-analyses of correlation coefficients, meta-analytic structural equation modeling), are well-suited for L2 reading research due to their componential nature. The present study reviews 14 meta-analyses on L2 reading comprehension published between 2010 and 2023, with a focus on their key study features and findings. While all of the 14 meta-analyses examined the relationship between one or more reading-related variables and L2 reading comprehension and yielded substantial convergence in their findings, their research focus and scope also varied widely, leading to some level of diversity in their scope of literature search, methods of analysis, and findings. We review our findings on the convergence and divergence of the study features across the 14 meta-analyses, summarize their key findings, and provide suggestions for future research.